2011
DOI: 10.1128/iai.00777-10
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A 4 Inhibits Porphyromonas gingivalis -Induced Aggregation and Reactive Oxygen Species Production by Modulating Neutrophil-Platelet Interaction and CD11b Expression

Abstract: Porphyromonas gingivalis is an etiological agent that is strongly associated with periodontal disease, and it correlates with numerous inflammatory disorders, such as cardiovascular disease. Circulating bacteria may contribute to atherogenesis by promoting CD11b/CD18-mediated interactions between neutrophils and platelets, causing reactive oxygen species (ROS) production and aggregation. Lipoxin A 4 (LXA 4 ) is an endogenous anti-inflammatory and proresolving mediator that is protective of inflammatory disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 72 publications
3
65
0
1
Order By: Relevance
“…Furthermore, in human neutrophils it has been found that TLR2 signalling induced Rac2 and Cdc42 activation [45]. Along this line, activation of TLR2 on the monocytic cell line THP1…”
Section: Platelet Activation Induced By Thrombin Via Pars or Collagenmentioning
confidence: 67%
“…Furthermore, in human neutrophils it has been found that TLR2 signalling induced Rac2 and Cdc42 activation [45]. Along this line, activation of TLR2 on the monocytic cell line THP1…”
Section: Platelet Activation Induced By Thrombin Via Pars or Collagenmentioning
confidence: 67%
“…The results suggest that a supplement of exogenous LXA4 could facilitate antiinflammatory actions that can decelerate progression of chronic inflammatory disorders, such as periodontitis and atherosclerosis (17).…”
Section: F Tarannum and M Faizuddinmentioning
confidence: 92%
“…Infectious agents that have been associated with CVD in epidemiological studies and also have been detected in plaque tissue include porphyromonas gingivalis, chlamydia pneumonia, herpes simplex virus and CMV (Epstein et al, 2000, Xenaki et al, 2009, Borgeson et al, 2011.…”
Section: Cytomegalovirus (Cmv)mentioning
confidence: 99%
“…CMV can also reside in endothelial cells and when activated give rise to elevated levels of ICAM-1, VCAM-1 and endothelial leukocyte adhesion molecule (ELAM)-1, which enhance the migration across the endothelium of circulating leukocytes, for instance CMV infected monocytes (Sedmak et al, 1994, Burns et al, 1999. CMV has also been proven to cause increased levels of acute phase proteins and cytokine production (Epstein et al, 2000, Borgeson et al, 2011. CMV infection of endothelial cells also causes expression of von Willebrand factor resulting in platelet activation and aggregation, which may lead to thrombosis formation (SoderbergNaucler, 2006).…”
Section: Cytomegalovirus (Cmv)mentioning
confidence: 99%